miRNAs and lncRNAs in tomato: Roles in biotic and abiotic stress responses - Li, Qian; Shen, Heng; Yuan, Shoujuan; Dai, Xigang; Yang, Changxian (Frontiers in Plant Science, 2023)
Plants are continuously exposed to various biotic and abiotic stresses in the natural environment. To cope with these stresses, they have evolved a multitude of defenses mechanisms. With the rapid development of genome sequencing technologies, a large number of non-coding RNA (ncRNAs) have been identified in tomato, like microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). Recently, more and more evidence indicates that many ncRNAs are involved in plant response to biotic and abiotic stresses in tomato. In this review, we summarize recent updates on the regulatory roles of ncRNAs in tomato abiotic/biotic responses, including abiotic (high temperature, drought, cold, salinization, etc.) and biotic (bacteria, fungi, viruses, insects, etc.) stresses. Understanding the molecular mechanisms mediated by ncRNAs in response to these stresses will help us to clarify the future directions for ncRNA research and resistance breeding in tomato.